Adiponectin and Sarcopenia: A Systematic Review With Meta-Analysis - Komici, Klara; Dello Iacono, Antonio; De Luca, Antonio; Perrotta, Fabio; Bencivenga, Leonardo; Rengo, Giuseppe; Rocca, Aldo; Guerra, Germano (Frontiers in Endocrinology, 2021)
Background: Sarcopenia is a progressive loss of skeletal muscle mass whose pathophysiology has been proposed to possibly involve mechanisms of altered inflammatory status and endocrine function. Adiponectin has been shown to modulate inflammatory status and muscle metabolism. However, the possible association between adiponectin levels and sarcopenia is poorly understood. In order to fill this gap, in the present manuscript we aimed to summarize the current evidence with a systematic review and a meta-analysis of studies reporting serum adiponectin levels in patients with sarcopenia compared to non-sarcopenic controls. Methods: An electronic search through Medline/PubMed, Cochrane Library and Science Direct was performed till 1 march 2020. From the included papers, meta-analysis of cross-sectional studies comparing serum levels of adiponectin between patients with sarcopenia and controls was performed. Results: Out of 1808 1370 initial studies, 5 7 studies were meta-analyzed. Sarcopenic participants had significantly higher levels of adiponectin Hedges's g with 95% CI 0.85 (0.64-1.07) p < 0.001, I2 98.98% than controls. Hedges's g with 95% Confidence Interval (CI) : 1.20 (0.19- 2.22), p = 0.02 than controls. Subgroup analysis, performed in Asian population and focused only on identification of the condition based on AWGS criteria, and DEXA evaluation, and reported higher adiponectin levels in sarcopenic population (1.34 (1.06-1.61), p < 0.001 and I2 99.43%, 0.71 (0.45-0.96), p < 0.001 and I2 99.08%, respectively). 2.1 (0.17-4.03), p = 0.03 and I2=98.98%. Meta-regression analysis revealed female gender to significantly influence the results as demonstrated by beta = 0.11 95% CI (0.01 0.22), p = 0.034. beta=0.14 95% CI (0.010-0.280), p=0.040. Conclusions: Our meta-analysis found evidence that sarcopenia is associated with higher adiponectin levels. However, caution is warranted on the interpretation of these findings and future longitudinal research is required to disentangle and better understand the topic.